2014
DOI: 10.1007/s10120-014-0339-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic completion total gastrectomy for remnant gastric cancer: a single-institution experience

Abstract: Background The aim of the present study was to evaluate the feasibility of laparoscopic completion total gastrectomy (LCTG) in patients with remnant gastric cancer. Methods Patients who underwent completion total gastrectomy for remnant gastric cancer between May 2003 and December 2012 were divided into two groups: an open completion total gastrectomy (OCTG) group and an LCTG group. Clinicopathological data, operative data, and patient survival rates were analyzed. Results Thirty-four remnant gastrectomies (17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 16 publications
2
56
2
Order By: Relevance
“…A total of 18 patients (18 %) had postoperative complications. Eight studies (67 of 100 patients) reported that no conversion to open surgery had been required, whereas one study reported a 47 % conversion rate to open surgery [10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 18 patients (18 %) had postoperative complications. Eight studies (67 of 100 patients) reported that no conversion to open surgery had been required, whereas one study reported a 47 % conversion rate to open surgery [10].…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded ten English-language publications on laparoscopic gastrectomy for remnant gastric cancer (Table 3) [6][7][8][9][10][19][20][21][22][23]. A summary of open surgery for remnant gastric cancer during this study period is also presented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies have compared laparoscopic completion total gastrectomy and open completion total gastrectomy (Table 4). [34][35][36] Laparoscopic completion total gastrectomy had similar surgical outcomes to open completion total gastrectomy, except the former had a significantly longer operative time. Laparoscopic completion total gastrectomy was technically feasible and reliable, but offered no definitive clinical advantage over open completion total gastrectomy.…”
Section: Laparoscopic-completed Total Gastrectomy For Remnant Gastricmentioning
confidence: 94%
“…Another presumed advantage of robotic gastrectomy is that the learning curve for robotic gastric surgery may be easier to learn compared to laparoscopic gastric surgery (41). The published number of cases representing the learning curve for laparoscopic gastric surgery is anywhere from 40 to 100 cases (42)(43)(44)(45).…”
Section: Robotic Surgery For Gastric Cancermentioning
confidence: 99%